Research Article: Efektivitas Pengobatan Herbal pada Pasien Hipertensi: Research Article: Effectiveness of Herbal Treatment in Hypertension Patiens - Audi Ichsani Ariwibowo; Indah Laily Hilmi; Salman Salman (Jurnal Surya Medika (JSM), 2023)
Hypertension is a condition in which blood pressure increases above normal limits. Treatment of hypertension can be done pharmacologically and non-pharmacologically. Non- pharmacological treatment through exercise, maintenance of diet and use of herbal ingredients. The purpose of this study was to determine the use of medicinal plants in hypertension sufferers. The research method used is literature study obtained from scientific articles searched through Google Scholar, PubMed, and Research Gate using the keywords Effectiveness, Herbal Medicine, Complementary Therapy and Hypertension. The criteria for the articles used have been published for 8 years, between 2014-2022, the title and contents of the journal are in accordance with the research objectives. The use of herbal medicine as an alternative medicine has become an everyday part of society. There are several herbal plants that are considered effective in lowering blood pressure in people with hypertension